Case study of water pollution in Podwiśniówka acid mine pit lake (Holy Cross Mts., Poland) - Suligowski, Roman; Molenda, Tadeusz; Ciupa, Tadeusz (Quaestiones Geographicae, 2023)
On the Holy Cross Mountains (southern Poland), located within the tectonic zone of the Trans-European Suture Zone (TESZ), numerous former quarries exist, including those of Cambrian quarzitic sandstones and sandstones with pyrite veins. This article presents the results of geochemical studies on the waters of the acidic mine pit lake Podwiśniówka (with an area of 1.5 ha and a maximum depth of 7.0 m) conducted in 2018. The tests were carried out in a vertical water column (every 1 m) in the central part of pit lake. The mean concentration of metals/metalloids, determined using inductively coupled plasma-quadrupole mass spectrometry (ICP-QMS), was found to form the following sequence in decreasing order: As> Cu> Ni> Co> Cr> Zn> U> Pb> Cd> Tl. With increasing depth, there was a general upwards trend in the concentrations of all the determined elements. In all cases, the average value of the single pollution index in the water column greatly exceeds the very strong level in relation to the geochemical background of surface waters globally (As – above 1250 times). The integrated pollution index for the ten trace elements in the water column increases with depth, and its average value exceeding 250 times the highest reference level. At the same time, the cluster analysis carried out showed the existence of two distinct depth zones in the pit lake: upper (0–4 m) and lower (5–7 m), differing in the scale of the water pollution.